Diseño de un plan de mercadeo para la Universidad de Ibagué para el año 2021 (2021)
This research it is carried out with the objective of designing a marketing plan for the University of Ibagué for the year 2021, analyzing communication, promotion and marketing processes to formulate strategies that allow position at the national and regional levels, increase its share of in the market and to have a greater number of students enrolled in undergraduate programs that offers, starting from an analysis of external and internal factors in order to analyze the main problem about the decrease in the number of students enrolled in universities. This research is conclusive-descriptive with a simple cross-sectional design with a quantitative methodology. One of the conclusions reached is that in the analysis of external factors identifies the risks of the economic recession that causes a drop in employment figures and is directly reflected in people's purchasing power, making it difficult to access higher education services in private universities. As a result of the current health emergency, unemployment increased, affecting the quality of life of many students who have had to leave their studies to help their families, so they leave their professional studies to enter working life.